(untitled) (Research, Society and Development, 2022)
The aim of this qualitative systematic review is to establish the relationship between SARS-CoV-2 infection and the appearance of oral manifestations. The results were obtained after extensive research and review of articles currently published on the subject in question. Studies claim that the mucosa of the oral cavity may be a high-risk route for SARS-CoV-2 infection, raising the hypothesis that lesions may develop in the oral cavity due to the virus infection. The most commonly reported changes are taste disorders such as dysgeusia, hypogeusia and ageusia. Mucous lesions, such as ulcers, erosions, mucositis, blister, macules and plaques, also found in affected patients, varying in quantity, appearance and location. Dry mouth sensation, TMJ disorders and opportunistic fungal and viral infections are reported in some cases. However, the direct cause-and-effect relationship between SARS-CoV-2 infection and the appearance of lesions in the oral cavity is still unclear. Authors defend that the general state of immunosuppression, stress and/or vascular alterations, inherent to COVID-19, may explain the arise these lesions. It is evident, therefore, that there is a relationship between COVID-19 and the development of dental lesions, but further studies are needed to understand the pathogenesis of these alterations.